Implementation of edge detection algorithm using FPGA reconfigurable hardware - Abd, Said (Maǧallaẗ al-abḥath al-handasiyyaẗ, 2020)
Digital image processing is known as computer manipulation of image, which includes algorithms like image enhancement and target reorganization. Some of these algorithms involve operations like convolution and edge detection, which requires high computation. Generally, the software running on processor performs these manipulations. To achieve higher computation performance in terms of execution time, these algorithms are implemented on reconfigurable hardware like FPGA. One can implement parallel architecture and pipelined architecture on FPGA to gain speed up. In this work, we provide a detailed description of implementing edge detection algorithm on SGI–RC100 platform. The algorithm is implemented using ANSI-C to manipulate the host program and Mitrion–C language. Mitrion–C offers efficient way to write code for parallel and pipelined architecture to preform edge detection. Then, the algorithm is tested on Intel Intanium 2 based architecture and compared its execution time with RC 100 platform based algorithm to check the speed up gain by FPGA based algorithm. The experimental results showed that the speed of the reconfigurable hardware FPGA based algorithm outperformed the software-based approach by more than 50 times. تعرف معالجة الصور الرقمية بأنها معالجة الكمبيوتر للصور و التي تتضمن خوارزميات مثل تحسين الصورة أو استخلاص بعض الخواص و المزايا تتضمن بعض هذه الخوارزميات عمليات مثل الالتواء و الكشف عن الحواف، الأمر الذي يتطلب إجراء حسابات عالية. بشكل عام، يقوم البرنامج الذي يتم تشغيله على المعالج بإجراء هذه الحسابات. لتحقيق أداء عالي من حيث وقت التنفيذ، يتم تنفيذ هذه الخوارزميات على أجهزة قابلة لإعادة التكوين مثل FPGA. يمكن للمرء تنفيذ هندسة متوازية و معمارية على FPGA لزيادة السرعة. في هذا العمل، نقدم وصفا مفصلا لخوارزمية تنفيذ الكشف عن الحافة على منصة SGI-RC100 . يتم تنفيذ الخوارزمية باستخدام ANSI-C لمعالجة البرنامج المضيف و لغة Mitrion-C. يوفر Mitrion-C طريقة فعالة لكتابة التعليمات البرمجية للعمارة المتوازية و الموضوعة في خط أنابيب لإجراء كشف الحافة. بعد ذلك، يتم اختبار الخوارزمية على بنية 2 Intel Intanium و مقارنة وقت التنفيذ مع الخوارزمية المستندة إلى منصة 100 RC للتحقق من زيادة السرعة من خلال الخوارزمية المستندة إلى FPGA. و أظهرت النتائج التجريبية أن سرعة خوارزمية FPGA القائمة على الأجهزة القابلة لإعادة التشكيل تفوقت على المنهج القائم على البرمجيات بأكثر من 50 مرة.